2010
DOI: 10.3109/0886022x.2010.486492
|View full text |Cite
|
Sign up to set email alerts
|

Mannitol is an independent risk factor of acute kidney injury after cerebral trauma: a case–control study

Abstract: We retrospectively studied a random cohort of patients with cerebral trauma to investigate the risk factors of acute kidney injury (AKI) following cerebral trauma. AKI was determined using the RIFLE (risk, injury, failure, loss, or end-stage kidney) staging criteria. About 171 patients were chosen in the study, with 53 patients in AKI group and 118 patients without AKI in non-AKI group. By logistic regression analysis, univariate analysis revealed that age, hypertension, emergent surgery, systemic inflammatory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
47
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(48 citation statements)
references
References 25 publications
0
47
0
1
Order By: Relevance
“…13,32 However, the relationship between AKI and preexisting renal impairment has not been explored among patients treated with mannitol. 9,15 Our results demonstrate that patients with preexisting renal dysfunction showed a significant chance of developing AKI. With normal renal function, the halflife of mannitol is approximately 70 minutes, increasing to as long as 36 hours in patients with uremia.…”
Section: Discussionmentioning
confidence: 60%
“…13,32 However, the relationship between AKI and preexisting renal impairment has not been explored among patients treated with mannitol. 9,15 Our results demonstrate that patients with preexisting renal dysfunction showed a significant chance of developing AKI. With normal renal function, the halflife of mannitol is approximately 70 minutes, increasing to as long as 36 hours in patients with uremia.…”
Section: Discussionmentioning
confidence: 60%
“…5,[11][12][13] In most cases, high-dose mannitol infusion was given. [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] During mannitol infusion, hyperosmolarity was documented by most, that is, 13 reports/series while combined hyponatremia and hyperosmolarity in 8 reports/series ( (Table 2). In our patient, it was up to 0.24 kg given over 4 days (56 hours) at a rate not faster than 0.5 g/kg/h.…”
Section: Resultsmentioning
confidence: 99%
“…17 In the setting of acute CNS (central nervous system) insult, two of the studies (Fang et al and Dziedzic et al) concluded that accumulative doses of mannitol is associated with MI-ARF while the other three (Chen et al, Gondim et al and Kim et al) suggested that mannitol is safe in patients with otherwise healthy kidneys and that MI-ARF appears to be associated with chronic insults to the kidneys such as diabetes or hypertension. 8,[17][18][19][20] Furthermore, Kim et al concluded that higher mannitol infusion rate is associated with more frequent and more severe AKI (acute kidney injury; Table 3). 18 …”
Section: Resultsmentioning
confidence: 99%
“…3). Clinical reports and animal experiments have shown that the use of edaravone, mannitol, or NSAIDs alone can cause acute renal failure [6][7][8][9][10][11][12]. Examination revealed that the patient received a score of nine on the Naranjo Adverse Drug Reaction Probability Scale [13], which indicated that the application of these drugs had a ''definite'' causal relationship with the acute kidney injury.…”
Section: Discussionmentioning
confidence: 99%